1989
DOI: 10.1073/pnas.86.23.9509
|View full text |Cite
|
Sign up to set email alerts
|

Detection of "deleted" mitochondrial genomes in cytochrome-c oxidase-deficient muscle fibers of a patient with Kearns-Sayre syndrome.

Abstract: Using in situ hybridization and immunocy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(98 citation statements)
references
References 28 publications
8
90
0
Order By: Relevance
“…COX‐deficient muscle fibers in patients with single, large‐scale mtDNA deletions have been consistently shown to accumulate high levels of mtDNA deletions 27, 35, 36. Accordingly, we have shown that deletion level increases with higher degrees of OXPHOS deficiency across a total of 673 fibers from 6 patients.…”
Section: Discussionmentioning
confidence: 54%
“…COX‐deficient muscle fibers in patients with single, large‐scale mtDNA deletions have been consistently shown to accumulate high levels of mtDNA deletions 27, 35, 36. Accordingly, we have shown that deletion level increases with higher degrees of OXPHOS deficiency across a total of 673 fibers from 6 patients.…”
Section: Discussionmentioning
confidence: 54%
“…Muscle biopsies from patients with KSS or CPEO show ragged-red fibers and cytochrome oxidase-negative fibers [58,59]. Clinical signs vary widely in different syndromes but include muscle weakness, heart block, retinopathy, deafness, diabetes, short stature and dementia [2,60].…”
Section: Discussionmentioning
confidence: 99%
“…Because deletions erase essential parts of the mitochondrial protein synthetic machinery (i.e. tRNAs) [58,61] as well as essential components of the respiratory chain complexes that produce energy and other metabolites for the cell (Figure 5), we expected a strong 'nuclear response' to the 'mitochondrial stimulus'.…”
Section: Discussionmentioning
confidence: 99%
“…Although no severe biochemical deficiency could be demonstrated, the cell-line appeared to be more sensitive to doxycycline than control cell-lines (Spelbrink et al 1994). Since different cells in a single culture generally contain different percentages of mutant mtDNA (Mita et al 1989;Matthews et al 1995), this meant that treatment with low concentrations of DC could, in principle, be used to select against those cells in culture harbouring the highest percentages of del-mtDNA, and thereby reduce the average percentage of del-mtDNA in culture. Previous findings had already indicated that the addition of low concentrations of DC resulted in a stronger inhibition of growth in cells with a high level of del-mtDNA compared to control lymphoblasts (Spelbrink et al 1994).…”
Section: Discussionmentioning
confidence: 99%